The art of sharing resources: How to distribute water during a drought period - Sebastian Cano-Berlanga; María-José Solís-Baltodano; Cori Vilella (Games, 2023)
Water scarcity is a growing problem in many regions worldwide. According to the United Nations, around one-fifth of the world's population lives in areas where water is scarce. Another one-quarter of the world's population has to face water supply cuts, mainly because this proportion of the population lacks the necessary infrastructure to acquire water from rivers and aquifers (UN, 2005). Water is a resource that is essential to human survival and is also present in all productive processes in the economy. Therefore, we are challenged to adequately manage water to ensure the population's well-being and to achieve socioeconomic development. Specifically, this paper analyzes the situation present in the summer of 2022 at Riudecanyes (a village in Catalonia, Spain), where a drought problem exists. We propose applying the conflicting claims problem theory to give possible solutions to distribute the water. We propose to use this theory to describe the distribution of the available irrigation hours in 2022, considering the demand made by the farmers in the previous year, when there was regular irrigation.
Keywords: 330; water scarcity; conflicting claims problems; drought